Rapid repellent potential of essential oil from Etlingera elatior Jack RM Smith against rice weevils of Sitophilus oryzae: A sustainable approach for pest control in stored rice - Diana Kertini, Monir; NURHAZIQAH, MD YAZID; Ming, Thian Jung; Rosmawati, Saat; Qammil Muzzamil, Abdullah; Mohamad Iskandar, Jobli (Malaysian Society for Microbiology, 2026)
Aims: Insect infestation of Sitophilus oryzae is detrimental for food storage, which has haunted the small-scale farmers for years. Growing resistance of S. oryzae against phosphine, restricted use and banning of certain insecticides in some countries have made these problems worse, demanding researchers seek greener ways for pest control. The present study examined the repellent effect of essential oil (EO) from Etlingera elatior against S. oryzae at concentrations of 2-8 µL/30 cm2 . Methodology and results: The EO was extracted using the hydro-distillation method and characterised by gas chromatography-mass spectrometry (GC-MS) technique. Repellent assay of EO was investigated against adult S. oryzae based on the filter paper impregnation method. Results revealed that E. elatior leaf and flower EO demonstrated strong repellent activity towards S. oryzae at 2 µL/30 cm2 after 2 h of exposure (p < 0.05). Rapid removal of S. oryzae was observed after 1 h exposure to leaf EO at an increased concentration of 8 µL/30 cm2 . Conclusion, significance and impact of study: The study indicates that E. elatior leaf and flower EOs have great potential to be developed as green insecticides for rapid removal of rice weevils in food storage applications. These findings provide important insights into pest control using green insecticides. Their rapid action and natural origin offer an environmentally sustainable approach to managing S. oryzae infestations in stored grain, benefiting small-scale farmers and promoting chemical-free pest control.